Encoding Systems and Evolved Message Processing: Pictures Enable Action, Words Enable Thinking - Lang, Annie (2015)
This paper, based on theories of ecological perception, embodied motivated cognition, and evolutionary psychology, proposes that pictures elicit evolved biologically imperative responses more quickly and thoroughly than do words. These biologically imperative responses are directly responsible for evolved automatic reactions away from biological threats (e.g. escaping predators, avoiding disease and noxious stimuli) and towards opportunities (e.g. consuming food, approaching mates, finding shelter) in the environment. When elicited, these responses take time to occur and may delay or interfere with other types of behavior. Thus, when environmental information is presented in pictures (which should elicit larger biological responses than words) biological responses should interfere more with higher order tasks like information processing and cognitive decision-making. To test this proposition we designed an experiment in which participants performed speeded categorizations of 60 pairs of matched pleasant and unpleasant environmental opportunities and threats. They categorized the items based on their form (is this a word or a picture?) or based on how the picture made them feel (is this pleasant or unpleasant to you?). If pictures do elicit greater biologically imperative responses than their word counterparts, participants should be able to make form decisions faster than feeling decisions, especially when presented with words rather than pictures and especially when the words and pictures have less biological relevance. This main proposition was supported. Implications for this proposition in terms of communication theory are discussed.